Kerapuhan Sel Darah Merah Sapi Bali (THE FRAGILITY OF ERYTHROCYTES OF BALI CATTLE) - ., Siswanto; Sulabda, I Nyoman; Soma, I Gede (Jurnal Veteriner, 2014)
An experimental study was conducted in order to evaluate the   of erythrocyte on bali cattle atVeterinary Physiology Laboratory, Faculty of Veterinary Medicine, Udayana University, Denpasar, duringone month.  Fifty blood samples were taken from bali cattle which slaughtered at Pesanggaran abattoir,Denpasar. The erythrocyte fragility was determined by using method Red Cell Fragility Procedure (2001).Results showed that the fragility (initial haemolysis) on red blood cell of bali cattle was observed, atranged between 0.45% - 0.55% NaCl , while for total  haemolysis range between  0.30 - 0,35 % NaCl.
Keywords: fragility, haemolysis, erythrocyte, cattle